2005
DOI: 10.1097/00002508-200505000-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Influence of Pain and Fatigue on Physical Performance and Health Status in Ambulatory Patients With Human Immunodeficiency Virus

Abstract: Pain has a substantial impact on physical performance and quality of life among ambulatory human immunodeficiency virus patients. Fatigue also impacts physical performance. Compromised ability to perform certain physical tasks affects quality of life. Further investigation of the roles of these relevant variables should be investigated in path analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 22 publications
0
50
0
2
Order By: Relevance
“…The total distance walked, in feet, in 5 min was recorded. This test has been shown to have high inter-rater reliability, high testretest reliability, and to correlate significantly with other indices of disability [42,43]. An index of objective (physical) clinical improvement was derived by computing the difference between the first (Week 1) and the second (Week 4) assessment periods on the measure of walking distance.…”
Section: Methodsmentioning
confidence: 99%
“…The total distance walked, in feet, in 5 min was recorded. This test has been shown to have high inter-rater reliability, high testretest reliability, and to correlate significantly with other indices of disability [42,43]. An index of objective (physical) clinical improvement was derived by computing the difference between the first (Week 1) and the second (Week 4) assessment periods on the measure of walking distance.…”
Section: Methodsmentioning
confidence: 99%
“…20 The tests complement self-reports of function and help to quantify the impact of symptom burden on function; they have been shown to have high interrater reliability and high testretest reliability and to correlate significantly with other indices of disability. 21,22 For the 5-minute walk, participants were asked to walk as quickly as possible, but at a comfortable speed, between two markers set 20 m apart. The distance walked in 5 minutes was recorded in metres.…”
Section: Physical Functionmentioning
confidence: 99%
“…Henderson, Safa, Easterbrook, & Hotopf (2005) actually found greater fatigue in individuals with higher CD4 counts. Some studies found no relationship between fatigue and HIV viral load (Barroso et al, 2003;Ferrando et al, 1998;Sullivan et al, 2003; Voss, 2002), whereas one found greater fatigue with a higher viral load (Simmonds, Novy, & Sandoval, 2005).Other immune abnormalities in HIV infection may influence the development and course of fatigue. Untreated HIV infection generally produces a state of heightened immune activation, as measured by CD8CD38 cells, whereas successfully treated patients usually show evidence of decreased immune activation.…”
mentioning
confidence: 99%